2019
DOI: 10.1002/14651858.cd012631.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Higher versus lower fraction of inspired oxygen or targets of arterial oxygenation for adults admitted to the intensive care unit

Abstract: Analysis 2.5. Comparison 2 Sensitivity analysis: all-cause mortality-at maximum follow-up, Outcome 5 All-cause mortality-at maximum follow-up-types of oxygen interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 140 publications
1
78
0
4
Order By: Relevance
“…This means that our prior beliefs will have minimal influence on the study results. Two sensitivity analyses will be conducted using evidence‐based (based on previous research) 2‐5 and sceptic priors for the parameters of interest; additional technical details on models and priors (including justifications) are presented in the supplement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that our prior beliefs will have minimal influence on the study results. Two sensitivity analyses will be conducted using evidence‐based (based on previous research) 2‐5 and sceptic priors for the parameters of interest; additional technical details on models and priors (including justifications) are presented in the supplement.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Cochrane review of lower versus higher oxygenation levels in adult ICU patients reported a statistically significant increase in mortality with higher oxygenation (relative risk (RR) 1.18, 95% confidence interval (CI): 1.01 to 1.37). However, the certainty of evidence was very low due to risk of bias, differences in oxygenation levels in the included trials, and sparse data 2 . The recent multicentre Intensive Care Unit Randomised Trial Comparing Two Approaches to Oxygen Therapy (ICU‐ROX) trial (n = 1000 adult ICU patients) demonstrated no difference in both 28‐day ventilator‐free days and mortality when comparing the conservative and usual oxygen therapy groups 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The oxygenation levels in patients admitted to intensive care units (ICUs) worldwide differ extensively . Several randomised clinical trials investigating the effects of a higher vs a lower oxygenation strategy for patients admitted to the ICU have been published throughout the last 5 years, the results, however, remain inconclusive . We present a detailed statistical analysis plan of the to date largest and still ongoing randomised clinical trial of higher vs lower oxygenation targets in the ICU, the handling oxygenation targets in the intensive care unit (HOT‐ICU) trial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a meta-regression effect of SpO 2 on in-hospital mortality showed an increased SpO 2 was associated with an increased risk of mortality. Barbateskovic et al [ 57 ] subsequently conducted another meta-analysis to evaluate the benefits and harms of higher versus lower F I O 2 or target PaO 2 in adult patients in ICU. They included a total of 10 RCTs with 1458 patients, and demonstrated that lower F I O 2 or target PaO 2 was associated with a marginal increase in the risk of mortality.…”
Section: Oxygen Concentration and Oxygen Toxicitymentioning
confidence: 99%